The travels of a t-shirt in the global economy an economist examines the markets, power and politics of world trade - Rivoli, Pietra (Wiley, 2006)
"In The Travels of a T-Shirt in the Global Economy, business professor Pietra Rivoli takes the reader on an around-the-world adventure to reveal the life story of her six-dollar T-shirt. Traveling from a West Texas cotton field to a Chinese factory, and from trade negotiations in Washington to a used clothing market in Africa, Rivoli examines international trade through the life story of this simple product. Combining a compelling story with substantive scholarship, Rivoli shows that both globalization's critics and its cheerleaders have oversimplified the world of international trade.